2003
DOI: 10.1029/2002gc000481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of glacial cycles and tectonics on natural subsidence in the Po Plain (Northern Italy): Insights from 14C ages

Abstract: [1] Samples rich in organic matter were collected from boreholes in the southern part of the Po Plain (Italy), a rapidly subsiding sedimentary basin. New 14 C dates, obtained from these samples, and 14 C data from the literature allowed for the evaluation of the rates of natural subsidence in the area. These range from 0 to 5 mm/yr. Most areas show rates around 1 and 2 mm/yr. The obtained subsidence rates are comparable with burial rates obtained from archaeological data. These data are interpreted in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 29 publications
4
51
2
1
Order By: Relevance
“…This study extends previous results by CARMINATI and DI DONATO (1999) that only accounted for the effects of remote ice sheets and used a viscosity profile which is probably inappropriate for the Mediterranean region (LAMBECK and PURCELL, 2005). Our improved evaluation of the GIA effects in the study area may be useful for the interpretation of the total natural subsidence in the Po plain and for the assessment of the anthropogenic component of sea level rise during recent decades (CARMINATI et al, 2003).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…This study extends previous results by CARMINATI and DI DONATO (1999) that only accounted for the effects of remote ice sheets and used a viscosity profile which is probably inappropriate for the Mediterranean region (LAMBECK and PURCELL, 2005). Our improved evaluation of the GIA effects in the study area may be useful for the interpretation of the total natural subsidence in the Po plain and for the assessment of the anthropogenic component of sea level rise during recent decades (CARMINATI et al, 2003).…”
Section: Introductionsupporting
confidence: 68%
“…In the bulk of the Mediterranean, this has been interpreted as mostly due to the effect of the isostatic disequilibrium induced by melt-water loading, while unloading from the Northern Hemisphere ice sheets may have affected the northern Adriatic region (LAMBECK and PURCELL, 2005;STOCCHI and SPADA, 2007). For the Po plain (northern Italy), it was suggested that approximately one half of the subsidence rates is related to tectonic processes and sediment loading or compaction, while glacio-isostatic adjustment (GIA) may account for the other half (CARMINATI et al, 2003). However, since the effects of GIA are sensitive to assumptions about mantle rheology and the time-history of ice sheets, providing upper and lower bounds even for a limited number of ice and rheological models may be more useful than giving point estimates as mostly done to date (e.g., CARMINATI and DI DONATO, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term natural subsidence is mainly the result of deep tectonics, glacial cycles and geodynamic movements [14]- [19]. Carminati et al [14] indicated the downflexure of the Adria plate as one cause of movement, at a maximum rate of 2.5 mm/year.…”
Section: State-of-the-art Of Subsidence In Northern Italy and Po Deltamentioning
confidence: 99%
“…Carminati et al [14] indicated the downflexure of the Adria plate as one cause of movement, at a maximum rate of 2.5 mm/year. The possible effects of tectonic activity along the northern Apennine thrust front buried under quaternary sediments was thoroughly discussed in [20].…”
Section: State-of-the-art Of Subsidence In Northern Italy and Po Deltamentioning
confidence: 99%
See 1 more Smart Citation